THE INTERFAITH MARRIAGE IN INDONESIA REVIEWED FROM A MAQASID SHARI’AH PERSPECTIVE - Sudarti, Sudarti; Najib, Ainun (Fakultas Syariah IAIN Ponorogo, 2023)
Abstract: Interfaith marriage has always been becoming a polemic, especially because of there is not yet awareness to impact long time toward own household and in society. Furthermore, it is so important to understand philosophically mean of forbidden interfaith marriage in perspective of maqasid ash-shari’ah. This study explains about interfaith marriage in perspective of maqasid ash-shari’ah as reflection efforts to consider benefits and damage, possibility bigger damage. There are two focus which is researched it. Firth, how is interfaith marriage in Islamic law and positive law in Indonesia. Second, how is reflection-analysis of maqasid ash-shari’ah to respond Islamic law and positive law.The results show that interfaith marriage, according to Islamic law and positive law, has been banned by them which is in line-relevant principles of maqasid ash-shari’ah on reflection-analysis. Base on reflection-analysis maqasid ash-shari’ah show that interfaith marriage, in side dharuriyah that will threaten the existence of priority descent-religion and soul, property and mind. Hajiyyah is to support and strengthen pro-Islamic law and positive law. Tahsiniyah is to educate people and society as preventive and participation to realize building a household which will become sakinah mawaddah warahmah finally. Keywords: Reflection; Interfaith marriage; Maqasid ash-shari’ah.